Linear and nonlinear topology optimization design with projection‐based ground structure method (P‐GSM). (19th February 2020) - Deng, Hao; To, Albert C.
Summary: A new topology optimization scheme called the projection‐based ground structure method (P‐GSM) is proposed for linear and nonlinear topology optimization designs. For linear design, compared to traditional GSM which are limited to designing slender members, the P‐GSM can effectively resolve this limitation and generate functionally graded lattice structures. For additive manufacturing‐oriented design, the manufacturing abilities are the key factors to constrain the feasible design space, for example, minimum length and geometry complexity. Conventional density‐based method, where each element works as a variable, always results in complex geometry with large number of small intricate features, while these small features are often not manufacturable even by 3D printing and lose its geometric accuracy after postprocessing. The proposed P‐GSM is an effective method for controlling geometric complexity and minimum length for optimal design, while it is capable of designing self‐supporting structures naturally. In optimization progress, some bars may be disconnected from each other (floating in the air). For buckling‐induced design, this issue becomes critical due to severe mesh distortion in the void space caused by disconnection between members, while P‐GSM has ability to overcome this issue. To demonstrate the effectiveness of proposed method, three different design problems ranging from compliance optimization to buckling‐induced mechanism design are presented and discussed in details.